"Naming Names" Equals Surveillance. Issue 2 (5th January 2019) - Unknown
Abstract : Creating even the impression of surveillance is an unfair labor practice, as shown by one recent case, Napleton Cadillac, 367 NLRB No. 6 (2018). The union alleged that management's identification of employee Oberg, as he walked by, as "the guy who started all this, " constitutes the creation of an impression of surveillance of union activities in violation of the Act.